Optimizing Zakat Governance to Reduce Multidimensional Poverty: Evidence from Indonesian Rural Communities - Moh. Ainur Rosyid (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2025)
This study examines how optimized zakat governance contributes to reducing multidimensional poverty across rural communities in Indonesia. Using a mixed-methods approach combining governance index scoring, household-level poverty metrics, and stakeholder interviews, the research assesses the effectiveness of institutional transparency, digital distribution systems, and beneficiary targeting mechanisms. The findings reveal that zakat institutions with strong governance frameworks particularly those emphasizing accountability, data-driven beneficiary verification, and integrated social programs achieve significantly higher poverty-alleviation outcomes. Enhanced digital platforms accelerate fund disbursement, reduce leakages, and improve alignment between community needs and program design. Moreover, the integration of productive-zakat schemes strengthens livelihood resilience by expanding micro-enterprise capacity and household income stability. The study concludes that optimizing governance is essential for transforming zakat from a charitable transfer into a strategic development instrument, offering empirical evidence relevant for policymakers, Islamic social finance practitioners, and rural development agencies.